Knockout of a putative ergothioneine transporter in Caenorhabditis elegans decreases lifespan and increases susceptibility to oxidative damage. (December 2013) - Cheah, I. K.; Ong, R. L. S.; Gruber, J.; Yew, T. S. K.; Ng, L. F.; Chen, C. B.; Halliwell, B.
Abstract: In addition to excretion of metabolic waste products, organic ionic transporters facilitate uptake of specific compounds of physiological importance. In animals, the organic cation transporter, OCTN1 was found to enable the specific uptake of the unique amino acid, ergothioneine (EGT). EGT can accumulate in the body at up to millimolar concentrations and is believed to function as a physiological antioxidant. However the main function of EGT and the reasons for its active accumulation in the body remain obscure. Through bioinformatic approaches, we identified an analogous EGT transporter in the nematode, Caenorhabditis elegans. The present study investigated and characterized deletion mutants of this gene, OCT-1, in the nematodes. Gene deletion mutations of the OCT-1 transporter were shown to decrease overall lifespan of the worms and increase oxidative damage. However the absence of impaired EGT uptake and the inability of excess EGT to rescue the debilitating phenotype indicate that EGT transport does not explain the deleterious effects of the gene deletion.